Modelo estratégico para la implementación de un sistema de gestión empresarial (ERP) para la PyME en México - Cortés Jiménez, Gilberto (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The enormous pressure on the quality not only in product but also in the service, comes the need to implement systems that meet the requirements of 100% quality and availability of internal and external information and thus obtain a business relationship with customers and suppliers that will provide an advantage to their competitors. Today, there are models of implementation for large companies, leaving aside for small businesses. Due to the lack of entrepreneurial culture and low orientation towards information technology for small businesses in Mexico, they suffer too many internal problems due to lack of a solid structure in its processes. This lack of technology and administrative structure have led to enormous weaknesses in the global market, where international companies are competing with better technology platform, leaving Mexican SMEs out of competition. At present, the globalization of businesses is leading companies to consider alternative solutions which in fact are nothing new but just have not been taken into account for their own benefit, such decisions are based on global demand overall quality of services and world class as they are called, all processes must be generated in a transparent and specific standards to comply with the business world, and thus participate in a competitive market. Enterprise Resource Planning or Business Management Systems (Enterprise Resource Planning, ERP) is a system composed of a set of standard components and modules that are capable of being tailored to each company. It is a way to use the information throughout the organization in key areas such as production, purchasing, inventory management and supply chain, financial control, human resources management, logistics and distribution, sales, marketing and customer relationship management.

La enorme presión sobre la calidad no sólo en el producto sino también en el servicio, viene la necesidad de implementar sistemas que cumplen con los requisitos de calidad del 100% y la disponibilidad de información interna y externa y así obtener una relación de negocios con clientes y proveedores que proporcionarán una ventaja a sus competidores. Hoy en día, hay modelos de implementación para las grandes empresas, dejando de lado a las pequeñas empresas. Debido a la falta de cultura emprendedora y baja orientación hacia la tecnología de la información para las pequeñas empresas en México, sufren demasiados problemas internos debido a la falta de una estructura sólida en sus procesos. Esta falta de tecnología y la estructura administrativa han dado lugar a enormes debilidades en el mercado global, donde las empresas internacionales están compitiendo con una mejor plataforma tecnológica, dejando a las pymes mexicanas fuera de concurso. En la actualidad, la globalización de los negocios está llevando a las empresas a considerar soluciones alternativas que en realidad no son nada nuevo, pero simplemente no han sido tomados en cuenta para su propio beneficio, tales decisiones se basan en la demanda global de la calidad general de los servicios y de clase mundial, ya que son llamada, todos los procesos se deben generar en unos estándares transparentes y específicas para cumplir con el mundo de los negocios, y así participar en un mercado competitivo. Planificación de recursos empresariales o Sistemas de Gestión Empresarial (Enterprise Resource Planning, ERP) es un sistema compuesto por un conjunto de componentes estándar y módulos que son capaces de ser adaptada a cada empresa.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2010-0152; Información; PYME; Requisitos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5942